Characterisation of Biological Properties and Bioactive Compounds of Endophytic Fungi Isolated from Gynura procumbens (Sambung Nyawa) - Haifa Arghnia, A. Jamal (2022)
The significant rise of new diseases and development of resistant pathogenic microorganisms have resulted in the increasing demand for bioactive compounds that can be used for the production of various pharmaceuticals. One of the sustainable sources of bioactive compounds is endophytic fungi which are known to have the ability to produce myriads of bioactive compounds with varying beneficial biological properties. Thus, this research was conducted to study the bioactive compounds and biological properties of endophytic fungi isolated from Gynura procumbens (Sambung Nyawa). A total of 12 over 45 isolated endophytic fungi were successfully identified. They were Diaporthe hongkongensis SN1, Phomopsis sp. SN2, Colletotrichum truncatum SN3, Mycoleptodiscus indicus SN4, Diaporthe longicolla SN5, Macrophomina phaseolina SN6, Beltraniella portoricensis SN7, Colletotrichum asianum SN8, Colletotrichum brevisporum SN9, Fusarium incarnatum SN10, Colletotrichum gloeosporioides SN11, and Pestalotiopsis sp. SN12. These isolates were tested for the production of extracellular enzymes such as amylase, protease, cellulase, lipase, and laccase. Among the isolates, only isolate SN9 was detected to produce all extracellular enzyme. Then, these isolates undergone fermentation process and were extracted using ethyl acetate and methanol. Folin-Ciocalteu and aluminium chloride methods were used to quantify the total phenolic content (TPC) and total flavonoid content (TFC) of ethyl acetate and methanolic fungal extracts, respectively. The highest TPC value for ethyl acetate and methanolic extracts were exhibited by isolate SN11 (87.0 ± 14.8 mg GAE/g) and isolate SN4 (35.0 ± 5.9 mg GAE/g) respectively. Meanwhile, the highest TFC value for ethyl acetate and methanolic extracts were shown by isolate SN6 (122.8 ± 11.0 mg QCE/g) and isolate SN4 (60.4 ± 9.5 mg QCE/g), respectively. The DPPH free radical scavenging assay was used to investigate the antioxidant properties of the extracts. The ethyl acetate extract of isolate SN6 showed high antioxidant activity, with an inhibition percentage of 86.60 ± 3.20% and an IC50 value of 104.25 ± 18.51 µg/mL. In contrast, the highest scavenging activity percentage of methanolic extract was shown by isolate SN4 (49.95 ± 11.58%). In addition, ferric reducing antioxidant power (FRAP) assay was performed to confirm the antioxidant capacity of the fungal extracts. The highest FRAP value for ethyl acetate and methanolic extract were observed from isolate SN6 (239.9 ± 66.2 mg Fe (II)/g) and isolate SN4 (44.7 ± 7.7 mg Fe (II)/g), respectively. The positive control used for DPPH and FRAP assays was 1 mg/mL ascorbic acid, while the negative control used was methanol. Some of the fungal extracts also exhibited inhibitory activity against pathogenic microorganisms such as Staphylococcus aureus, Methicillin Resistant Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli and Salmonella typhi with minimum inhibitory concentration and minimum bactericidal concentration of 2500 – 5000 µg/mL and 5000 µg/mL, respectively. The positive and negative control used were 1 mg/mL tetracycline and 1% DMSO, respectively. Besides that, gas chromatography mass spectrometry analysis was conducted to identify the bioactive compounds present in the fungal extracts. Various bioactive compounds such as heptadecane, 2,6,10,15-tetramethyl- (17.82%), 9-Octadecenoic acid (Z)-, methyl ester (11.18%), hexadecane (10.40%), pentadecanoic acid, 14-methyl-, methyl ester (9.87%), oleic acid (9.24%), 2-Coumaranone (8.18%), and many other compounds were identified. The findings of this study clearly indicated that the endophytic fungi isolated from the leaves of G. procumbens possesses the ability to exhibit antioxidant and antibacterial activities besides capable of producing several beneficial bioactive compounds. These findings can contribute greatly to the pharmaceutical and medicinal industries in order to improve the effort to curb the rise of current maladies.